Uji Efektivitas Zeolit Alam Lampung Sebagai Agen Antibakteri Masker Wajah Terhadap Propionibacterium acnes - Idra Herlina; Shekinah Glory Aurellia Siregar; Roja Riliyanda Putra; Anna Azzahra Ismail; Tiarmauli Natalia Purba; Ashyfa Ramadhani; Aditya Ayu Wulanda; Mariyam; Muhammad Yogi Saputra; Edwin Rizki Safitra (Jurnal Inovasi Teknik Kimia, 2026)
Acne vulgaris is a common skin disorder caused by clogged pores and infection by Propionibacterium acnes. The use of synthetic chemicals in skincare products often leads to side effects, highlighting the need for safer and eco-friendly natural alternatives. Natural zeolite, particularly Lampung Natural Zeolite (ZAL), has potential as an antibacterial agent due to its porous structure and adsorption capacity. This study evaluates the effectiveness of ZAL as an active ingredient in clay mask formulations against P. acnes. ZAL was activated and purified, then formulated into masks with varying concentrations (2.5 g, 5 g, and 7.5 g). Characterization was conducted using IR, XRD, and SEM, while antibacterial activity was tested using the agar diffusion method. Activation improved crystallinity and increased silanol (Si–OH) groups, enhancing antibacterial performance. The 5 g zeolite formulation showed the largest inhibition zone, indicating optimal effectiveness. Overall, ZAL demonstrates strong potential as a natural antibacterial agent for facial mask products.